Uji Uji Aktivitas Antibakteri Ekstrak Etanol, Fraksi n-Heksan Dan Etil Asetat Daun Seminyak (Champereia manillana (Blume) Merr.) Terhadap Bakteri Enterococcus faecalis - Alvin Pratama; Haris Munandar Nasution; Ainil Fithri Pulungan; Zulmai Rani (Journal of Pharmaceutical and Sciences, 2026)
Background: Bacterial resistance to antibiotics has become a global concern, prompting the exploration of alternative antibacterial agents derived from natural sources. Enterococcus faecalis is a pathogenic bacterium frequently associated with root canal treatment failure due to its high resistance level. Seminyak leaves (Champereia manillana (Blume) Merr.) are known to contain secondary metabolites with potential antibacterial activity; however, studies based on solvent fractionation remain limited. Objective: This study aimed to evaluate the antibacterial activity of the ethanol extract, n-hexane fraction, and ethyl acetate fraction of seminyak leaves against Enterococcus faecalis. Methods: An experimental study was conducted through plant identification, preparation of simplicia, extraction using the maceration method with 96% ethanol, and liquid–liquid fractionation using n-hexane and ethyl acetate. Phytochemical screening was performed qualitatively and confirmed by thin-layer chromatography (TLC). Antibacterial activity was assessed using the disc diffusion method at concentrations of 15%, 30%, and 45% with three replications. Dimethyl sulfoxide (DMSO) 10% was used as the negative control, while chlorhexidine (standard concentration) served as the positive control. Data were analyzed using One-Way ANOVA followed by Tukey HSD post hoc test. Results: Phytochemical screening revealed that the ethanol extract contained alkaloids, flavonoids, tannins, saponins, and steroids. The n-hexane fraction predominantly contained nonpolar compounds (alkaloids and steroids), while the ethyl acetate fraction contained more diverse semi-polar compounds. Antibacterial testing showed that all samples exhibited activity against Enterococcus faecalis. The highest inhibition zone diameters at 45% concentration were 14.1 ± 0.21 mm (ethanol extract), 10.3 ± 0.17 mm (ethyl acetate fraction), and 8.5 ± 0.14 mm (n-hexane fraction). Statistical analysis indicated significant differences among treatments (p < 0.05). Conclusion: The ethanol extract, ethyl acetate fraction, and n-hexane fraction of seminyak leaves exhibit antibacterial activity against Enterococcus faecalis. The ethanol extract showed the highest activity, followed by the ethyl acetate and n-hexane fractions. These findings suggest that antibacterial compounds are more dominant in polar to semi-polar fractions.